2017
DOI: 10.1002/pssc.201600199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of Cu2Sn1−xGexS3

Abstract: Cu2SnS3 (CTS) is a promising compound for use as an absorber layer in thin‐film solar cells because it is made up of low‐cost and abundant elements. However, the band gap energy of 0.94 eV for monoclinic Cu2SnS3 is less than the optimal value for absorber layers in single‐junction solar cells. On the other hand, the band gap energy of Cu2GeS3 (CGS) is approximately 1.5–1.6 eV. Therefore, in this study, we carried out the synthesis of Cu2Sn1−xGexS3, which is a solid solution of Cu2SnS3 and Cu2GeS3. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…In fact, in a similar chalcogen compound, Cu 2 (Sn, Ge)S 3 , the same process has been reported to shift Raman peaks to higher frequencies. 28) This further supports the idea that, in our study, part of Sn was substituted with Ge to form Ge x Sn 1−x S. In addition, since no peaks attributed to GeS 29) were observed in the Raman spectra, it can be concluded that no segregation of GeS occurred near the surface.…”
Section: Resultssupporting
confidence: 90%
“…In fact, in a similar chalcogen compound, Cu 2 (Sn, Ge)S 3 , the same process has been reported to shift Raman peaks to higher frequencies. 28) This further supports the idea that, in our study, part of Sn was substituted with Ge to form Ge x Sn 1−x S. In addition, since no peaks attributed to GeS 29) were observed in the Raman spectra, it can be concluded that no segregation of GeS occurred near the surface.…”
Section: Resultssupporting
confidence: 90%
“…However, the surface Cu concentrations of the as-prepared specimens were significantly lower than would be expected regardless of the synthesis route. This surface Cu deficiency suggested the segregation of Cu-deficient secondary phases such as Cu 2 Sn 3 S 7 29,39 at the surface, as was reported in a previous paper. 6 Cu-deficient surface layers such as this have been demonstrated to improve the photovoltaic performances of Cu chalcogenides 40−42 and so would also be expected to have positive effects in the present photocathode system as well, rather than unfavorable factors such as the formation of recombination centers.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…Reported band gap energy of CTGS is higher than that of CTS. 9,15) However, the estimated band gap energies are equal or less than that of CTS. The estimated lower band gap energy is considered to be due to the absorption of the graphite-rich layer.…”
Section: Transmittance and (Ahν) 2 -Plotsmentioning
confidence: 88%
“…From the peak shift of 0.44 deg, the chemical composition ratio of Ge/(Sn+Ge) is estimated as 0.57. 9,14) 3.2. SEM and EPMA Figures 2(a) and 2(b) show a cross-sectional SEM image and a surface SEM image of the sulfurized sample at 600 °C, respectively.…”
Section: Xrd Patternsmentioning
confidence: 99%
See 1 more Smart Citation